GLP-1 and Underlying Beneficial Actions in Alzheimer’s Disease, Hypertension, and NASH - Li, Qiu-Xuan; Gao, Han; Guo, Yue-Xin; Wang, Bo-Ya; Hua, Rong-xuan; Gao, Lei; Shang, Hong-Wei; Lu, Xin; Xu, Jing-Dong (Frontiers in Endocrinology, 2021)
Derived from intestinal L cells, GLP-1 is dissevered by the enzyme dipeptidyl peptidase-4 (DPP-4) and takes effects through binding to GLP-1R. It is emerged as an incretin hormone since its discovery for it could facilitate the release of insulin and reduce insulin resistance (IR). However, apart from stimulating insulin secretion, GLP-1 possesses broader pharmacological effects such as anti-inflammatory, neuro-protection, regulating blood pressure (BP) and reducing lipotoxicity, which are interconnected to physiological and pathological process of Alzheimer's disease (AD), hypertension and non-alcoholic steatohepatitis (NASH). Currently, underlying mechanism of GLP-1 multiple effects are still not fully illustrated and a better understanding of these effects may help identify promising therapeutic targets of AD, hypertension and NASH. Therefore, we focus on biological characteristics of GLP-1, render an overview on the mechanism of GLP-1 effects in diseases and ventilate feasible therapeutic presumption of GLP-1 analogues in related diseases in this review.